Local Cosmopolitanism: Imagining and (Re-)Making Privileged Places - Van Assche, Kristof (Springer, 2015)
This book offers a unique perspective on cosmopolitanism, examining the ways it is constructed and reconstructed on the small scale in an ongoing process of matching the local with the global, a process entailing mutual transformation. Based on a wide range of literatures and a series of case studies, it analyzes the different versions and functions of cosmopolitanism and points to the need to critically re-examine current conceptions of globalization.